Pengembangan Soal Literasi Keuangan di Tingkat SMP Berbasis Google Sites - Faiq, Wang Achmad Althof; Fiangga, Shofan (MATHEdunesa, 2025)
Financial literacy is defined as knowledge, skills, and beliefs, which influence attitudes and behaviors to improve the quality of decision-making and financial management to achieve the financial welfare of the community. According to the results of the financial literacy survey on students aged 15-17 years, it shows that the composite financial literacy index is 51.7%, which is quite far behind when compared to the employee group where the composite financial literacy index is 83.22%. This study aims to describe the process of developing Google Sites-based financial literacy questions at the junior high school level and produce 14 Google Sites-based financial literacy questions at the junior high school level. This research is development research using the ADDIE model. The type of data in this study is quantitative data which is in the form of data analysis of the validity of financial literacy questions based on validator assessments, readability test analysis data based on student questionnaire results, and analysis data of question item validity and question reliability based on student test results. In this study, the data collection techniques used were expert validation questionnaires, readability questionnaires, and student test result data. This research developed 14 questions on financial literacy, 3 questions were declared invalid which were then eliminated by the researcher. The results of this study are to produce 11 valid and reliable financial literacy questions at the junior high school level based on Google Sites. Thus, teachers can develop digital-based financial literacy questions independently by paying attention to the developments carried out in this research.